2001
DOI: 10.1002/1099-0690(200101)2001:2<261::aid-ejoc261>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Maremycins C and D, New Diketopiperazines, and Maremycins E and F, Novel Polycyclicspiro-Indole Metabolites Isolated fromStreptomycessp.

Abstract: New diketopiperazines, named maremycins C 1 /C 2 (1a/1b) and D 1 /D 2 (2a/2b), as well as the novel spiro-indoles, maremycins E (3) and F (4), have been detected alongside the known maremycin B (6) in the culture broth of Streptomyces sp. (strain GT 051237) by chemical screening. The structures have been determined by detailed NMR spectroscopic investigations of the isolated metabolites. Maremycins C 1 /C 2 (1a/1b) as well as D 1 /D 2 (2a/2b) are diastereomers and were [a] Hans-Knöll-Institut für Naturstoff-F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(24 citation statements)
references
References 15 publications
0
24
0
Order By: Relevance
“…A great number of compounds bearing oxindole moieties are reported to possess significant antibacterial, antiprotozoal, antiinflammatory and antitumor properties [6,7], and they have been widely employed as potential synthons for the synthesis of alkaloids, drug candidates and clinical pharmaceuticals [8][9][10]. Isatin-based alkylation is one of the most important strategies for the construction of oxindole skeleton, especially for those bearing a hydroxyl substituent at the C-3 position which also possess various bioactivities [11,12]. Compared with Friedel-Crafts alkylation of indole with isatin for access to the monosubstituted 3-indolyl-3-hydroxy oxindoles [13][14][15], related study on alkylation of aminopyrazole was rare, although pyrazole had also been confirmed to provide privileged scaffolds in lead identification/drug discovery programs as well as therapeutically useful compounds in fields such as cyclooxygenase inhibitors (e.g., SC-558, tepoxalin, and celecoxib) and cannabinoid-1 inverse agonists which are very promising for reducing obesity (e.g., rimonabant) [16].…”
mentioning
confidence: 99%
“…A great number of compounds bearing oxindole moieties are reported to possess significant antibacterial, antiprotozoal, antiinflammatory and antitumor properties [6,7], and they have been widely employed as potential synthons for the synthesis of alkaloids, drug candidates and clinical pharmaceuticals [8][9][10]. Isatin-based alkylation is one of the most important strategies for the construction of oxindole skeleton, especially for those bearing a hydroxyl substituent at the C-3 position which also possess various bioactivities [11,12]. Compared with Friedel-Crafts alkylation of indole with isatin for access to the monosubstituted 3-indolyl-3-hydroxy oxindoles [13][14][15], related study on alkylation of aminopyrazole was rare, although pyrazole had also been confirmed to provide privileged scaffolds in lead identification/drug discovery programs as well as therapeutically useful compounds in fields such as cyclooxygenase inhibitors (e.g., SC-558, tepoxalin, and celecoxib) and cannabinoid-1 inverse agonists which are very promising for reducing obesity (e.g., rimonabant) [16].…”
mentioning
confidence: 99%
“…We have also studied the effect of the cation structure in HMAs on the N → M interaction using 15 N NMR method (in biomimetic conditions), for example, in Recently, HMA with М = Ni, Co were claimed as cocatalysts for photocatalytic preparation of hydrogen from water, [86] and those with М = Cu were proposed as the catalysts for arylhalides hydroxylation. [87] We have studied for the first time the HMA [nN (CН 2 СН 2 ОН) m М] p+ . (Cl − ) p , (where M = Co, Ni, Rh; n = 1,2; m = 1-3; p = 2,3) as the catalysts for hydrosilylation of phenylacetylene and styrene (Scheme 9).…”
Section: Hydrometallatranesmentioning
confidence: 99%
“…Spiro[cyclohexane-1,3′-indoline] is one of the most privileged motifs, which is not only featured in many naturally occurring alkaloids but also exists in various synthetic pharmaceutical compounds, displaying a broad spectrum biological activity, such as antimicrobial, anticancer, and anti-inflammatory activity. 1 For example, gelsemine is an effective agent for treatment of both neuropathic pain and sleep disturbance in partial sciatic nerve ligation mice. Satavaptan shows a good effect on maintaining normal sodium level.…”
Section: Introductionmentioning
confidence: 99%